Raw potato starch alters the microbiome, colon and cecal gene expression, and resistance to Citrobacter rodentium infection in mice fed a Western diet - Smith, Allen D.; Chen, Celine; Cheung, Lumei; Dawson, Harry D. (Frontiers in Nutrition, 2023)
Resistant starches (RS) are fermented in the cecum and colon to produce short-chain fatty acids and other microbial metabolites that can alter host physiology and the composition of the microbiome. We previously showed that mice fed a Total Western Diet (TWD) based on NHANES data that mimics the composition of a typical American diet, containing resistant potato starch (RPS), produced concentration dependent changes to the cecal short-chain fatty acids, the microbiome composition as well as gene expression changes in the cecum and colon that were most prevalent in mice fed the 10% RPS diet. We were then interested in whether feeding TWD/RPS would alter the resistance to bacterial-induced colitis caused by Citrobacter rodentium (Cr), a mouse pathogen that shares 66.7% of encoded genes with Enteropathogenic Escherichia coli. Mice were fed the TWD for 6 weeks followed by a 3-weeks on the RPS diets before infecting with Cr. Fecal Cr excretion was monitored over time and fecal samples were collected for 16S sequencing. Mice were euthanized on day 12 post-infection and cecal contents collected for 16S sequencing. Cecum and colon tissues were obtained for gene expression analysis, histology and to determine the level of mucosa-associated Cr. Feeding RPS increased the percentage of mice productively infected by Cr and fecal Cr excretion on day 4 post-infection. Mice fed the TWD/10% RPS diet also had greater colonization of colonic tissue at day 12 post-infection and colonic pathology. Both diet and infection altered the fecal and cecal microbiome composition with increased levels of RPS resulting in decreased α-diversity that was partially reversed by Cr infection. RNASeq analysis identified several mechanistic pathways that could be associated with the increased colonization of Cr-infected mice fed 10% RPS. In the distal colon we found a decrease in enrichment for genes associated with T cells, B cells, genes associated with the synthesis of DHA-derived SPMs and VA metabolism/retinoic acid signaling. We also found an increase in the expression of the potentially immunosuppressive gene, Ido1. These results suggest that high-level consumption of RPS in the context of a typical American diet, may alter susceptibility to gastrointestinal bacterial infections.